The assessment of thinking skills in chemistry for secondary school students in Malaysian classrooms - Jumahat, Tajulashikin; Nagappan, Rajendran; Nordin, Mohamad Sahari; Hussien, Suhailah; Othman, Nooraini (Universiti Teknologi Malaysia,Skudai, Johor, 2016)
This exploratory study developed a measure of classroom assessment called Test of Thinking Skills in Chemistry (TOTSIC) for secondary school students in Malaysia. The framework used for test specification is based on alternative taxonomy, which derived from Bloom’s Cognitive Taxonomy. The alternative taxonomy of thinking had been redefined and categorized into lower-order and higher-order thinking skills. Seventy items of the initial version of TOTSIC were assembled and constructed based on this alternative taxonomy, and have been confirmed by the experts in chemistry subject. Apart from that, item analysis procedure has refined the test into forty items in the final version. The internal consistency of the overall scale as well as LOTS and HOTS items were found to be adequate for multiple-choice format. In the field test, the overall attainment of students from the test was found to be slightly below average. Unfortunately, only a small percentage of the students were having a respectable performance in HOTS items. This study suggests that TOTSIC is a viable preliminary measure for thinking skills in chemistry that can be applied as a formative assessment instrument in classroom settings. However, there is a room for improvement to assess students’ level of thinking skills in chemistry primarily for HOTS items. Most importantly, the current study is advocating the immersion of higher-order thinking skills among students as stipulated in the Malaysia Educational Blueprint 2013-2025.